FORMATION OF SKILLS FOR INDEPENDENT EXERCISES IN PHYSICAL EXERCISES FOR STUDENTS OF THE PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2010)
The research reveals the fact that the majority of students positioning themselves as healthy people have skills of independent training in physical exercises. Most of such students have grown up in the families where parents didn't take part in physical activities.
Keywords: skill; independent training; physical exercises